Kemampuan Literasi STEM pada Calon Pendidik Fisika: Analisis Komprehensif Menggunakan Teori Pengukuran Rasch - Muhammad Zaky; Astija; Supriyatman; Muslimin; Mohammad Jamhari; Ratman (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to measure and analyze the level of STEM literacy among prospective physics educators using Rasch measurement theory. A quantitative approach with a descriptive design was employed. The research instrument consisted of a STEM literacy test comprising multiple-choice questions and essays, and the data were analyzed using Winstep software version 5.7.1 to assess the validity and reliability of the measurement instrument. The results reveal that only a small number of prospective physics educators exhibit very high STEM literacy, while the majority demonstrate moderate to low levels of competencies and attitudes toward STEM literacy. The measurement instrument was confirmed to be valid and reliable according to Rasch parameters. These findings highlight the need for targeted interventions to enhance digital literacy, multidisciplinary skills, technology integration, and scientific competence among aspiring educators. Educational institutions are thereby urged to better prepare future educators to teach and promote STEM literacy effectively among students.